Iceland and Europe: Is the discourse changing? - Ólafur Árni Jónsson 1987- (2019)
The focal point of this thesis was Brexit, and the possible influence it has had on the European discussion in Iceland. Brexit has had immense consequences, both inside and outside of Britain. Britain is on its way out of the European Union, the third biggest nation in the Union. It will take some time for events to unfold completely, both Britain and the European Union will have to adapt but I‘m interested in the effects this has on Iceland. The European discussion in Iceland has been shaped by the same discourse for some time now, and it is interesting to see if Brexit forces it to change or evolve in some way. My method of choice was inductive content analysis; I analyzed both articles and speeches by actors involved in the European discussion. Both Euroskeptic and Pro-European side is represented in the analysis. Before I discuss my research analysis, I gloss over Brexit and what it is, explain the European discourse pre-Brexit and the nationalist rhetoric that often follows. The research did return some interesting findings, notably the increased populist rhetoric in discourse that is perhaps caused by the increased populism in Europe and Britain.